2021
DOI: 10.3390/vaccines9060674
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Side Effects Associated with COVID-19 Vaccines in Saudi Arabia

Abstract: Background: Pfizer-BioNTech and Oxford-AstraZeneca are recently introduced vaccines to combat COVID-19 pandemic. During clinical trials, mild to moderate side effects have been associated with these vaccines. Thus, we aimed to evaluate short-term post-vaccination side effects. Methods: Cross-sectional, retrospective study using an online questionnaire was conducted among COVID-19 vaccines recipients in Saudi Arabia. General and demographic data were collected, and vaccine-associated side effects after receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
124
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(194 citation statements)
references
References 17 publications
33
124
6
Order By: Relevance
“…Abu-Hammad et al, 2021 found that the mRNA-based vaccine was significantly associated with local side effects, while the viral vector-based vaccine was associated with systemic side effects among Jordanian healthcare workers [ 32 ]. On the contrary, Alhazmi et al, 2021 found no significant difference in terms of local side effects among vaccinated individuals in Saudi Arabia; however, the viral vector-based vaccine was still significantly associated with an increased risk of systemic side effects [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abu-Hammad et al, 2021 found that the mRNA-based vaccine was significantly associated with local side effects, while the viral vector-based vaccine was associated with systemic side effects among Jordanian healthcare workers [ 32 ]. On the contrary, Alhazmi et al, 2021 found no significant difference in terms of local side effects among vaccinated individuals in Saudi Arabia; however, the viral vector-based vaccine was still significantly associated with an increased risk of systemic side effects [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the vast majority of governments rely on more than one vaccine in their mass-vaccination strategies, there is a lack of evidence on the comparative side effects of different COVID-19 vaccines [ 34 , 35 ]. The current evidence is limited by a series of constraints, including unequal sample size across the study groups, lack of normal distribution of demographic and medical risk factors across the study groups, and lack of attention to the onset of each side effect [ 30 , 31 , 32 , 33 , 36 ]. Vaccine selectivity can be defined as “the discriminatory attitudes towards certain types of vaccines based on their target contagion or manufacturing technology that yields heterogeneous acceptance levels of recommended vaccines”.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several independent (non-sponsored) phase IV studies on mRNA-based COVID-19 vaccines have been published from various countries, e.g., Czech Republic, Germany, Greece, Iraq, Italy, Jordan, Malta, Poland, Saudi Arabia, the UK, and the USA [13,[19][20][21][22][23][24][25][26][27][28][29][30]. The results of these phase IV studies generally agreed with the results of the phase III trials executed by the manufacturers and published by the regulators, i.e., the Centers for Disease Control and Prevention (CDC) [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…There is no prior study documenting the interplay between health risks, safety recommendations, and media selection [ 3 , 16 ]. However, to our knowledge, this is the first study that identifies the most effective source and message attributes for scheming the COVID-19 vaccination awareness campaigns [ 11 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…), and self-efficacy. This research initially recognizes the benefits, barriers, and threats of COVID-19 from the literature, then defines the cues to action, including disclosure to a persuasive message via media contents such as public service messages (a form of advertising), to promote willingness to take the COVID-19 vaccine [ 11 , 26 , 27 ]. Recent studies underpinning the HBM suggest that the efficacious administration of COVID-19 relies on the effective dissemination of factual information by activating cognitive mechanisms [ 28 ].…”
Section: Introductionmentioning
confidence: 99%